Rancangan Pembelajaran Berkarakteristik dan Inovatif Abad 21 pada Materi Gelombang dengan Model Pembelajaran Discovery Learning di SMKN 1 Dukuhturi - Agung, Purnomo; Sutji, Muljani (Universitas Pancasakti Tegal, 2022)
The learning model is applied in the teaching and learning process by teachers in schools. The Legal Basis for the preparation of RPP curriculum 2013 is the Regulation of the Minister of Education and Culture No. 22 of 2020 on Process Standart and Permendikbud No.103 of 2020 on Learning in Primary and Secondary Education. Learning Implementation Plan (RPP) use by Teachers using several learning models, one of which uses the Discovery Learning (DL) model, Problem Based Learning (PBL) and Project-Based Learning (PjBL) model. Before determining the learning model to be used in learning activities, there are several things that teachers must consider in choosing it, namely: Consideration of the goals to be achieved, considerations related to learning materials or materials, considerations from the point of view of learners or students, other considerations that are nontechnical.